Gingival crevicular fluid levels of human beta-defensin 1 in individuals with and without chronic periodontitis - Costa, L. C.M.; Soldati, K. R. [UNESP]; Fonseca, D. C.; Costa, J. E.; Abreu, M. H.N.G.; Costa, F. O.; Zandim-Barcelos, D. L. [UNESP]; Cota, L. O.M. (Wiley, 2018)
Background and Objective: Human beta-defensins (hBDs) contribute to innate immunity antimicrobial activity. They are also effective in the adaptive immune response and may play a crucial role in the susceptibility to diseases of the oral cavity. This study aimed to evaluate the levels of hBD-1 in the gingival crevicular fluid of individuals with and without chronic periodontitis. Material and Methods: Twenty periodontally healthy individuals (H) and 20 individuals with chronic periodontitis were recruited. Gingival crevicular fluid samples were collected from: healthy sites (Hh) from periodontally healthy individuals; and healthy sites (Ph), sites with gingivitis (Pg), and sites with periodontitis (Pp) from individuals with periodontitis. The levels of hBD-1 (pg/mL) were measured using enzyme-linked immunosorbent assay. Comparisons of hBD-1 between individuals (H and chronic periodontitis) and among sites (Hh, Ph, Pg, Pp) were performed through hierarchical linear modeling. Results: Gingival crevicular fluid levels of hBD-1 were: Hh = 229.52 ± 138.96 (median 199.26), Ph = 53.88 ± 58.17 (median 35.75), Pg = 57.11 ± 40.18 (median 39.90) and Pp = 55.31 ± 37.28 (median 54.19). No influence of site diagnosis (level 1; health/gingivitis/periodontitis) was observed; however, individual diagnosis (level 2; health/periodontitis) influenced the levels of hBD-1 (P <.001). Conclusion: Periodontally healthy individuals showed higher gingival crevicular fluid levels of hBD-1 when compared to individuals with chronic periodontitis. This suggests a potential protective role of hBD-1 in the susceptibility to chronic periodontitis.
Keywords: beta-defensins; chronic periodontitis; ELISA (enzyme-linked immunosorbent assay); gingival crevicular fluid